Standard operating procedures for sweetpotato breeding data management. COP Breeding Data Management SweetGAINS - Wanjohi, L.; Eyzaguirre, R.; Boeck, B. de (International Potato Center, 2020)
Current modernization efforts of sweetpotato breeding operations in Africa establish a new mindset. A modern sweetpotato breeding program continuously generates vast amounts of data on which it depends for all decision making throughout the program. Without a proper systematization of efforts, it is likely that significant mistakes can be unwillingly made, which would impact in a negative manner both genetic gains and the adoption of new varieties by smallholders. This document describes standard operating procedures (SOPs) for implementing breeding data workflows to ensure that all necessary breeding data are recorded appropriately and made easily accessible. This document needs to be considered as an alive one, as through its ensuing iterations additional SOPs will be added, and the current ones would be modified to reflect the learnings acquired. The data management SOPs in this volume cover the following key sweetpotato breeding data workflows: phenotyping, crossing, quality assessment, germplasm management, and DNA sample management. A relational database, SPBase (www.sweetpotatobase.org)1, plays a central role as a breeding data management system across workflows. Several other digital tools have been developed to connect to SPBase to facilitate recording and uploading different types of data.